Comments on "The Cenozoic fold‐and‐thrust belt of Eastern Sardinia: Evidences from the integration of field data with numerically balanced geological cross section" by Arragoni et al., 2016. Issue 2 (31st January 2017) - Berra, F.; Lanfranchi, A.; Jadoul, F.
Abstract: Arragoni et al. (2016) suggest in their paper published on tectonics that the carbonate succession of Eastern Sardinia represents a Cenozoic fold‐and‐thrust belt, related to the Alpine orogenesis. According to these authors, this supposed fold‐and‐thrust belt represents the southward continuation of the Alpine Corsica collisional chain and the missing link between the Alpine Chain and the Calabria‐Peloritani domain. Field evidence and the published literature document instead that all the surfaces that Arragoni et al. interpret as thrust are actually stratigraphic contacts. The balanced geological section of Arragoni represents thus a geometric exercise missing the basic data needed to nurse the proposed model, and it does not reflect the geology of Eastern Sardinia. The data provided by Arragoni et al. (2016) do not support the presence of an Alpine thrust‐and‐fold belt in Eastern Sardinia, and this paper may suggest to the geological community a misleading interpretation of the geodynamic evolution of the Alpine and Mediterranean area. Key Points: The paper published by Arragoni et al. 2016 suggests the existence of a Cenozoic fold‐and‐thrust belt in Eastern Sardinia Field evidence indicates that the suggested tectonic contacts are stratigraphic boundaries There is no Cenozoic fold‐and‐thrust belt in Eastern Sardinia